Strategi Diferensiasi Warung Kelontong Multi-Layanan : Inovasi Layanan Transaksi Digital dalam Menciptakan Keunikan Bersaing di Kawasan Padat Pesaing - Irma Iqlima Nurussa’ban; Anfas Anfas (Jurnal Strategi Bisnis Teknologi, 2025)
This research aims to throughly explore the differentiation strategy model implemented by the small-medium enterprise (SME) grocery store of  "Yussandi Komunika," in integrating digital transaction services such as prepaid credits, electricity tokens, and e-wallet top-ups, as an effort to create a competitive advantage. The background of the problem is driven by the highly competitive conditions in densely populated areas, where traditional grocery stores are compelled to transform in order to maintain their business relevance.Digital service innovation, presented through an adaptive and user-focused platform, has proven to be a core competency that is difficult to imitate and rare, simultaneously providing a sustainable competitive advantage. This innovation not only addresses the challenges of densely populated conditions but also establishes a new standard for efficiency and customer experience in a competitive market.The effective differentiation model for multi-service grocery stores in highly competitive areas is not solely based on price, but rather on a combination of services and the quality of interpersonal service. The store transforms into a "mini service point" offering one-stop shopping convenience for customers. The main differentiation strategies identified include: (1) Core Service Differentiation (offering comprehensive PPOB (Payment Point Online Banking) services and e-wallet balance availability), (2) Personnel Differentiation (quality of communication and speed of friendly service), and (3) Image Differentiation (creating a perception as a trustworthy and modern store).